Variable viscosity and thermal conductivity effects on heat transfer by natural convection from a cone and a wedge in porous media (Archives of Mechanics - Test, 2003)
The problem of steady, laminar heat transfer by natural convection flow over a vertical cone a wedge embedded in a uniform porous medium with variable viscosity and thermal conductivity is investigated. The transformed governing equations are solved numerically by using a finite difference scheme. The obtained results are compared with earlier papers on special cases of the problem and are found to be in excellent agreement. The influence of porous medium inertia effect, viscosity variation parameter ðœ– and thermal conductivity variation parameter γ on the fluid velocity and temperature is discussed. Including the porous medium inertia effect or viscosity variation parameter in the mathematical model is predicted to reduce the local Nusselt number. Furthermore, the local Nusselt number increases in the presence of thermal conductivity variation parameter.